The COVID-19 Pandemic in Chiba Prefecture, Japan and Viet Nam: A Lesson-learned in COVID-19 Pandemic Control in These Two Populations - KANA, Furuuchi; Ono, Yumi; CHHEANG, Limeng; YUMA, Okada; YOUSUKE, Nagai; TAKEUCHI, Miu; HIROTOSHI, Kuga; Duyen, Le Hoa; Hlaing, Thaingi; Ngoan, LE Tran (Asian Pacific Journal of Environment and Cancer, 2020)
Aims: The study aimed to describe and compare the status of COVID-19 occurrence in Chiba prefecture and Viet Nam to recommend lesson-learned in COVID-19 control between two populations. Methods: We used the official database of COVID-19 published online by the Chiba Prefectural Government, and the Viet Nam Ministry of Health. The database’s variables include ID, age, gender, residence, sources of infection, the onset date of symptoms, and the positive confirmation date. The observation period starts on 23 January 2020, when the first positive patient appeared in Viet Nam and the end on 13 July 2020. Results: There were 1,166 and 373 positive cases, giving the estimated number of positive cases per million persons was 186.2 and 3.9 in Chiba and Viet Nam, respectively. The ratio of asymptomatic patients to those with symptomatic in Viet Nam is much higher than Chiba prefecture (3.14 vs. 0.15). In Chiba, there were two waves of COVID-19 occurrence; the first wave reached a peak on 28 Mar. 2020 with 64 positive cases and the second wave reached a peak on 11 Jul. 2020 with 29 positive patients. In Viet Nam, the first local case was on 23 Jan. 2020 and the last local case was on 16 Apr. 2020. During the last 88 days, from 16 Apr to 13 Jul. 2020, there were no local positive cases. Conclusions: The findings suggest that the prohibition of unnecessary commuting, meeting at the public places, and night outings of the 20-60 age group of people should be very effective in preventing infection spread. More importantly, as a lesson-learned from Viet Nam, we need to take action of testing, tracing, isolating suspected people who have closely contacted the confirmed positive cases, and quarantine people at the port of entry and immigration as fast as possible before the situation gets worse.